Evaluation of Content on Commonly Used Web sites About Induction of Labor and Pain Management During Labor. Issue 5 (September 2018) - English, Cara L.; Alden, Kathryn R.; Zomorodi, Meg; Travers, Debbie; Ross, Malcolm S.
Abstract: Purpose: The Internet is a common source of information for women during pregnancy. A multitude of data about birth can be found on the Internet, yet there are few guidelines to direct women to credible Web sites. Providers are often unaware of the health sites their patients access. The purpose of this study was to evaluate the quality of the written content on Web sites about induction of labor and pain management during labor. Study Design and Methods: Descriptive study of 11 Web sites on induction of labor and pain management during labor. Searches on Google, Yahoo, and Bing were used to identify Web sites women use to seek information about labor and birth. The Web sites were evaluated using the Health Information Technology Institute (HITI) criteria, readability, and content criteria from UpToDate, an evidence-based, healthcare professional-authored clinical resource. Results: No Web sites met all the HITI criteria for both topics. One Web site was written at or below a seventh-grade reading level and six were written at or above a ninth-grade level. Although there was no perfect Web site, we noted government Web sites provided the highest quality information. Clinical Implications: Evaluation and discussion of Web sites used by pregnant women is needed. Nurses and other healthcare providers should be aware of what information exists and what Web sites women are using so they can guide women to credible, evidence-based data. Directing women to government-sponsored Web sites on childbirth topics may help them access accurate information. Abstract : Childbearing women often look to the Internet for information about pregnancy, labor, birth, and parenting. However, some of the information may be inaccurate or of limited value. In this study, the content and accuracy of common Internet sites used by pregnant women were evaluated. Websites hosted by the government were found to be the most complete and accurate.